What impact does microfinance loan have on incomes of the rural poor in Nigeria? - Kasali, Taofeek Aremu; Ahmad, Siti Aznor; Lim, Hock Eam (IISTE, 2015)
The problem of poverty has attracted specific programmes within the circle of Government administrations particularly in Sub-Saharan Africa. One of such programmes is the development strategy tool of provision of microcredit to the poor through Microfinance Institutions (MFIs). Although the issue of the influence of Microfinance loan on poverty reduction has been discussed by some scholars, little efforts have been made to assess the impact of MFIs at the grassroots particularly on those who live in the rural areas.This paper therefore intends to fill the gap in literature by examining the impact of microfinance loan on poverty reduction through the dimension of rural poor income. To achieve this objective, the study adopted multi-stage random sampling technique to collect primary data through the structured questionnaire. A total sample of 1,134 microfinance loan beneficiaries and non-beneficiaries were used as respondents from three states in South- West Nigeria. Descriptive Statistics and Multiple Regression Model were explored to describe the characteristics of the sample for the study and evaluate the impact.The results revealed that microfinance has negligible income effects on the rural poor in Nigeria.To this end, the Government is advised to provide necessary amenities that will encourage MFIs to establish branches in the rural areas; and implement more supportive services like education and training on entrepreneurship and health facilities. MFIs should engage cheap labour available in the rural areas and train them for effective performance and easy penetration to the rural poor. .